LINGUPOETICS OF SIMILARITIES USED IN CHILDREN'S POETRY - Sobirova Dilafruz (Scholar Express Journals, 2021)
The article discusses the emergence of analogy, one of the means of artistic expression, which has a special place in Uzbek children's poetry, and its formation on the basis of children's age, thinking, worldview, psychology, attitude to the environment, animate and inanimate objects; the child is shown to have a stable place in speech; the analogies are divided into thematic groups and explained between examples.
Keywords: Uzbek children's poetry; simulation; morphological simulation; exical-semantic simulation